Knowledge of Breast Self Examination among Female Students in Ignatius Ajuru University of Education, Rivers State - Emma, Elechi (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
The study investigated knowledge regarding breast self-examination (BSE) among female undergraduate students of Ignatius Ajuru University of Education, Port Harcourt, Rivers State, Nigeria during 2014 and 2015 academic session. A descriptive survey research design in the study was employed. The sample comprised 300 students selected from the six female hostels in the main campus of the university using a proportionate random sampling technique. Data were collected with structure questionnaire, with reliability co-efficient of 0.71. Data analysis was done using descriptive statistics. It was found out that most (72.7%) respondents were aware of BSE. The electronic media were the major sources of information while the health worker was reported low. The respondents had 79.6% knowledge of BSE. It was recommended among others that public awareness on the importance of BSE be intensified using the mass media and that health workers should promote BSE during contacts with female patients/clients.